Timetable planning and scheduling system - Ann, Alvin De Sheng (2014)
In this report, a details design process and implementation of the project, Timetable Planning and Scheduling (TPS) System will be discussed. The TPS system is a web-based application that is used to schedule courses that is offered by the School of Computer Engineering (SCE). The TPS system should be simple to use, user friendly, so that it will enable the staff to schedule courses easily.